2015
DOI: 10.1016/j.sbspro.2015.01.229
|View full text |Cite
|
Sign up to set email alerts
|

Financial Education and Financial Literacy in the Czech Education System

Abstract: This paper reacts to the current situation in our society and the need for financial education in schools and for adults. Today's world demands financial and economic literacy. This paper outlines the importance of economic and financial literacy in primary and secondary schools (ISCED 1, 2, 3) in the Czech Republic. Research findings in the Czech Republic and from the World Bank have shown high levels of household debt while also indicating the need for higher levels of financial education. Financial literacy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(46 citation statements)
references
References 4 publications
0
30
0
16
Order By: Relevance
“…This advantage arises partly from the fact that the Czech Republic has implemented a national financial literacy strategy (Opletalova, 2015(Opletalova, , p.1177 , Table 1). Although our survey suggested that the form of financial education and knowledge verification did not significantly affect the results, it is plausible that the systematic character and especially the continuity of financial education may have a positive impact.…”
Section: Discussionmentioning
confidence: 99%
“…This advantage arises partly from the fact that the Czech Republic has implemented a national financial literacy strategy (Opletalova, 2015(Opletalova, , p.1177 , Table 1). Although our survey suggested that the form of financial education and knowledge verification did not significantly affect the results, it is plausible that the systematic character and especially the continuity of financial education may have a positive impact.…”
Section: Discussionmentioning
confidence: 99%
“…Karena pengalaman dengan instrumen keuangan berdampak lebih banyak dalam pengetahuan keuangan (Peng, Bartholomae, Fox, & Cravener, 2007). Dalam meningkatkan literasi keuangan beberapa metode yang sering digunakan adalah games, role playing, ceramah, kunjungan ke lembaga keuangan dan pelatihan langsung dari lembaga keuangan dan akademisi terpercaya (Dhany, 2018;Walstad et al, 2010;Opletalova, 2015;Dewi & Safaah, 2018).…”
Section: Pendahuluanunclassified
“…OECD mengemukakan bahwa pendidikan keuangan adalah proses dimana konsumen (masyarakat, investor, akademisi, dan para ekonom) ingin meningkatkan pengetahuan, pemahaman, aplikasi, dan kemampuan analisis mereka terhadap produk atau konsep keuangan melalui informasi, instruksi dan/atau saran obyektif dalam mengembangkan keterampilan dan kepercayaan diri, sehingga menjadi lebih sadar akan risiko dan peluang keuangan, menentukan pilihan, mencari solusi, dan mengambil tindakan efektif lainnya untuk meningkatkan kesejahteraan finansial mereka (Berry, Karlan, & Pradhan, 2018;Meier & Sprenger, 2013; Pengaruh Self-Reliance dan Self-Efficacy terhadap Pendidikan Keuangan Mahasiswa Opletalová, 2015). Selain itu, pendidikan keuangan mempunyai peran untuk mencegah dan mengendalikan hutang, serta meningkatkan tabungan dan investasi (Giofré, 2017;Silva, Magro, Gorla, & Nakamura, 2017).…”
Section: Pendahuluanunclassified